2018
DOI: 10.1007/s11883-018-0706-1
|View full text |Cite
|
Sign up to set email alerts
|

Premature Coronary Heart Disease in South Asians: Burden and Determinants

Abstract: South Asians have demonstrated a higher burden of premature CAD (PCAD) compared with other ethnicities. These findings are not limited to non-immigrant South Asians but have also been found in immigrant South Asians settled around the world. In this article, we first discuss studies evaluating PCAD among South Asians residing in South Asia and among South Asian immigrants in other countries. We then discuss several traditional risk factors that could explain PCAD in South Asians (diabetes, hypertension, dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Our observations for the South Asian group are consistent with those from prior reports in both the Asian subcontinent, as well as in other Western countries of destination, where South Asians consistently showed a very high prevalence of metabolic abnormalities, especially diabetes, and of premature and aggressive CHD 5 8 14–17. A number of potential underlying mechanisms have been proposed, including genetic predisposing factors, cultural and lifestyle determinants such as low levels of physical activity or diets rich in highly atherogenic fat, and metabolic factors such as abdominal adiposity, insulin resistance, high-density lipoprotein cholesterol abnormalities or high levels of Lp[a], among others 5 8 14–21…”
Section: Discussionsupporting
confidence: 91%
“…Our observations for the South Asian group are consistent with those from prior reports in both the Asian subcontinent, as well as in other Western countries of destination, where South Asians consistently showed a very high prevalence of metabolic abnormalities, especially diabetes, and of premature and aggressive CHD 5 8 14–17. A number of potential underlying mechanisms have been proposed, including genetic predisposing factors, cultural and lifestyle determinants such as low levels of physical activity or diets rich in highly atherogenic fat, and metabolic factors such as abdominal adiposity, insulin resistance, high-density lipoprotein cholesterol abnormalities or high levels of Lp[a], among others 5 8 14–21…”
Section: Discussionsupporting
confidence: 91%
“…In general, there seems to be a global rise in the incidence and prevalence of atherosclerotic diseases. But, a premature and rapidly progressive (“malignant”) involvement of the coronary arteries occurs in South Asia, particularly India (15.4% in our series), and this is seen not only in individuals settled in that region but also in the immigrant population, with a lower incidence of less than 3% seen in the Western population [9]. Predictably, males (84.5%) outnumbered women (15.5%).…”
Section: Discussionmentioning
confidence: 77%
“…Predictably, males (84.5%) outnumbered women (15.5%). Hypertension, DM, smoking, dyslipidemia, obesity, sedentary life style and positive family history continue to be the traditional risk factors [4, 9]. Hypertension and/or DM was noted in 40.5%, while a history of smoking was documented in only five patients.…”
Section: Discussionmentioning
confidence: 99%
“…South Asians, or people who trace their ancestry to the Indian subcontinent, have been observed to exhibit higher indicators of cardiometabolic risk relative to White populations [ 8 ]. The region has seen an epidemiological shift from communicable to noncommunicable diseases (NCDs) in the last few decades due to improved socioeconomic conditions and high rates of rural to urban migration [ 9 ]. Studies have shown that the South Asian ethnicity is associated with higher incidence of CHD [ 10 ].…”
Section: Introductionmentioning
confidence: 99%